Fluorographdiyne: A Metal‐Free Catalyst for Applications in Water Reduction and Oxidation. Issue 39 (7th August 2019) - Xing, Chengyu; Xue, Yurui; Huang, Bolong; Yu, Huidi; Hui, Lan; Fang, Yan; Liu, Yuxin; Zhao, Yingjie; Li, Zhibo; Li, Yuliang
Abstract: A highly efficient bifunctional metal‐free catalyst was prepared by growth of three‐dimensional porous fluorographdiyne networks on carbon cloth (p‐FGDY/CC). Our experiments and density functional theory (DFT) calculations show the 3D p‐FGDY/CC network is highly active and it is a high potential metal‐free catalyst for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), as well as overall water splitting (OWS) under both acidic and alkaline conditions. The experimental and theoretical results show very good consistency; for example, in the HER process, p‐FGDY/CC exhibits small overpotentials of 82 and 92 mV to achieve 10 mA cm −2 under alkaline and acidic conditions, respectively. This ensures an even higher selectivity for the adsorption/desorption of various O/H intermediate species. The essential key promotion accomplishes a bifunctional H2 O redox performance application under pH‐universal electrochemical conditions. Abstract : Fine‐tuning energy levels : A three‐dimensional porous fluorographdiyne network on carbon cloth serves as an active metal‐free catalyst for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), as well as overall water splitting (OWS) under acidic as well as alkaline conditions. The strong F−C bonding modifies the local p–p coupling, which affects the filling of the electronic orbitals.